Pengaruh Pengaturan Individu Proses Crossover Dan Mutasi Algoritme Genetika Pada Kasus Travelling Salesman Problem - Sean Coonery Sumarta (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
One disadvantage in the genetic algorithm is the number of iterations in the search for the optimum solution. This caused long computation time. This study aimed to obtain the best method to determine the individual parent crossover operator and mutation Genetic Algorithm in the case of the Traveling Salesman Problem (TSP). the results obtained in this research with a set of individuals in the process of crossover and mutation can reduce the number of iterations. So as computing time can be even faster